Poor Adherence to Secondary Prophylaxis is Associated with More Severe Rheumatic Valve in Pediatric Patients: A Cross-Sectional Study - Taufieq Ridlo Makhmud; Mohammad Saifur Rohman; Renny Suwarniaty; Djanggan Sargowo; Faris Wahyu Nugroho; Annisa Hasanah; Bambang Kusbandono; Citra Tarannita; Ratih Kusuma Wardani; Sasmojo Widito; Heny Martini (Heart Science Journal, 2020)
Background : Rheumatic heart disease (RHD) contributed to a large number of proportion amoung cardiovascular problems in developing county, especially Indonesia. Secondary prophylaxis method using intramuscular injection of Benzathin Penicillin-G (BPG) has been known as the most effective strategy in the prevention of RHD. However, whether this prevention method also resulting in prevention of disease severity in Indonesian patients remained to be examined.Objectives : This study aimed to assess the difference of rheumatic valve severity in Indonesian pediatric patients between adequate and poor adherence to secondary prophylaxis by using intramuscular BPG injection.Methods : This cross-sectional study was conducted at Pediatric Cardiology Department of Saiful Anwar General Hospital from November 2018 to June 2019. Patients with documented history of RHD were included. Frequency of intramuscular BPG injection during the last one year was recorded. Adherence was measured using the proportion of days covered (PDC) and adequate adherence was defined as PDC ≥0.90. The severity of RHD was assessed based on the severity of the mitral and / or aortic valve using echocardiography. Bivariate analysis and multivariate logistic regression analysis was used to identify characteristics associated with rheumatic valve severity.Results : A significant difference of rheumatic mitral and/or aortic valve severity was observed between adequate adherence compared to poor adherence group (p = 0.016). Rheumatic mitral and/or aortic valve were found to be more severe in patients who has one or more episode of ARF recurrence (p = 0.003). Multivariate logistic regression analysis demonstrated that adherence to secondary prophylaxis within the last 1 year has the strongest influence on the severity of rheumatic mitral and/or aortic valve (p = 0.049; OR 7.20).Conclusion : The adherence to secondary prophylaxis has the strongest related the rheumatic valve severity compared to other factors.